A Panel Study of Attitudes toward Ethnic Minorities and the Role of Changes in Individuals' Economic Situations. (25th March 2022) - Hendriks, Inge; Lubbers, Marcel; Scheepers, Peer
Abstract: This study applies the dynamic perspective of realistic conflict theory to assess whether and the extent that individuals' negative attitudes toward ethnic minorities changed and were linked to changes in individuals' economic situations. Employing Dutch panel data, we found that negative attitudes toward ethnic minorities were remarkably stable. Differences in attitudes toward ethnic minorities were more pronounced between individuals than within individuals. The small changes that did occur over the 10-year study period were hardly explained by economic characteristics. Only increased individual dissatisfaction with the national financial situation was associated with more negative attitudes. These results cast doubt on whether attitudes toward ethnic minorities are susceptible to change and raise questions about realistic conflict theory's relevance in explaining attitudinal change.